2022
DOI: 10.15252/embj.2021109300
|View full text |Cite
|
Sign up to set email alerts
|

c‐Maf enforces cytokine production and promotes memory‐like responses in mouse and human type 2 innate lymphoid cells

Abstract: Group-2 innate lymphoid cells (ILC2s), which are involved in type 2 inflammatory diseases such as allergy, can exhibit immunological memory, but the basis of this ILC2 "trained immunity" has remained unclear. Here, we found that stimulation with IL-33/IL-25 or exposure to the allergen papain induces the expression of the transcription factor c-Maf in mouse ILC2s. Chronic papain exposure results in high production of IL-5 and IL-13 cytokines and lung eosinophil recruitment, effects that are blocked by c-Maf del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…MAF, which is expressed selectively in macrophages, positively regulates IL10 production in these cells after stimulation with LPS [ 15 ]. Similarly, it has been reported that MAF induces cytokine production [ 16 ] and promotes IL10-mediated anti-inflammatory responses through inhibition of the inflammasome [ 17 ]. Finally, another recent study showed that MAF , in addition to participating in the control of IL10 production and lipogenesis, is a negative regulator of IL2, which modulates Th1, Th2 and Th17 immune responses in a context-specific manner [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAF, which is expressed selectively in macrophages, positively regulates IL10 production in these cells after stimulation with LPS [ 15 ]. Similarly, it has been reported that MAF induces cytokine production [ 16 ] and promotes IL10-mediated anti-inflammatory responses through inhibition of the inflammasome [ 17 ]. Finally, another recent study showed that MAF , in addition to participating in the control of IL10 production and lipogenesis, is a negative regulator of IL2, which modulates Th1, Th2 and Th17 immune responses in a context-specific manner [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the ILC2 marker genes segregating toward the top of this list, corresponding to enhanced epigenomic activity in the RAG naïve cells, tended to be genes previously identified to play positive roles in development, expansion, and activation of lymphoid cells. These included transcriptional regulators such as Tox [75][76][77][78] , Rora 38,51,[61][62][63] , Maf 19,58,59 , and Gata3 19, [50][51][52] , which are involved in early differentiation of both ILCs and lymphocytes (Fig. S9A).…”
Section: Ilc2s With a History Of Rag Expression Are Epigenomically Su...mentioning
confidence: 99%
“…ILC2 activation is not only characterized by the secretion of type-2 cytokines and IL-10, but also by the specific production of amphiregulin (AREG), a ligand of the Epidermal Growth Factor Receptor (EGFR), which has been shown to have multiple roles in cancer progression and inflammatory responses [36][37][38] . For these reasons, we quantified AREG in CML sera at onset and observed a slight but significant increase in the patients (Supplementary Figure S4D).…”
Section: Tumor-derived Vegf-a Stimulates Ilc2 Effector Functionsmentioning
confidence: 99%